REFERENCE POINTS OF THE PATHOGENESIS OF THE PHENOMENON OF MODEL FORMATION RISKY REPRODUCTIVE BEHAVIOR TEENAGE GIRLS - Ирина Вячеславовна Бабенко-Сорокопуд (Мать и дитя в Кузбассе)
Protection of the reproductive health of teenage girls and women is one of the priority medical and social tasks in the whole world, including the Donetsk region